Prediksi Financial Distress pada Industri Farmasi Indonesia: Pendekatan Altman Z-Score Periode Pandemi - Susetyo, Maria Christha Dianing Ratri; Lestari, Fransiska Wahyu (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2025)
The level of company health is very important for companies in running their business, so that the ability to earn profits can continue to be improved in order to avoid potential financial distress, such as a situation where the company's finances are getting worse day by day so that the company is unable to pay its debts to creditors. This case will have an effect on companies, especially pharmaceutical industry companies. The pharmaceutical business is a business with products that people always need. The pharmaceutical industry is the fourth largest contributor to the country's economy, especially Indonesia in the non-oil and gas manufacturing industry. This study aims to determine the financial condition of pharmaceutical subsector manufacturing companies listed on the IDX for the 2020-2023 period. The analytical tool used in this study is the Altman Z-Score method with predetermined financial ratio calculations.The result of this study concludes that from the seven manufacturing companies in the pharmaceutical subsector, the financial condition of each company in 2020-2023 did not experience financial distress or was in a healthy condition. Meanwhile, the company that has the highest average value for the X4 ratio (share market value) is PT. Sido Muncul Herbal & Pharmaceutical Industry, Tbk and the company that has the lowest average ratio value is PT. Phapros, Tbk (PEHA).